Structural and optical properties of samarium doped silica borotellurite glasses for optical switching application - Asyikin, A.S.; Latif, A.A.; Halimah, M.K.; Zaid, M.H.M.; Kamarudin, M.A.; Faznny, M.F.; Nazrin, S.N.; Zaitizila, I. (Elsevier Ltd, 2024)
The quaternary 56TeO2-24B2O3-(20-x)SiO2-xSm2O3 (x = 0.01, 0.02, 0.03, 0.04 and 0.05 M fraction) glasses were fabricated by using melt quenching method. XRD analysis reveals the amorphous nature of the prepared glass samples. FTIR and deconvolution studies show that Sm2O3 influences the modification of the glass network in the silica borotellurite glass system. The optical band gap and Urbach energy increases and decreases respectively with the addition of Sm2O3 beyond 0.02 M fraction. The overall refractive index of the glass system decreases along with the decrement in polarizability and optical basicity. The synthesized glass samples possess metallization criterion values of 0.30399 to 0.31068 which indicates that the glasses can be used for non-linear applications. The nonlinear behaviour of the fabricated samples which include the nonlinear absorption coefficient, nonlinear refractive index, and third order susceptibility attributed to changes in the glass structure. Silica borotellurite glass doped with 0.05 M fraction of samarium oxide that have 1.01 as the FOM value is advantageous for application in all-optical switching (AOS) devices.